Ailanthone reverses multidrug resistance by inhibiting the P-glycoprotein-mediated efflux in resistant K562/A02 cells - Han, Fang; Liu, Guoqiang; Sun, Caifeng; Wei, Jienan (Cellular and Molecular Biology, 2018)
Multidrug resistance (MDR) poses a great impediment to cancer treatment. Excessive expression of ATP-binding cassette transport protein AC-1 (P-glycoprotein, P-GLP) is usually involved in MDR. In this study, ailanthone (AIL), a natural compound extracted from the whole seedlings of Ailanthus altissima (Simaroubaceae) was shown to mediate the reversal of P-GLP-induced MDR and restore the susceptibility of K562/A02 cells to doxorubicin (DOX). Further mechanistic studies revealed that AIL increased intracellular DOX accumulation and interrupted Rh123 efflux through suppression of P-GLP, and also suppressed P-GLP ATPase activity. At the same time, it markedly inhibited MDR1 gene expression and P-GLP protein to sensitize the cytotoxic effect of DOX. Furthermore, AIL down-regulated P-GLP expression by inhibiting the PI3K/Akt pathway. Thus, AIL could be a potential therapeutic compound for reversing P-GLP-mediated drug resistant cancer.